FAKTOR-FAKTOR YANG BERPENGARUH PADA KINERJA BELANJA PEMERINTAH DAERAH KABUPATEN/KOTA DI PROVINSI BALI - Sumawan, I Wayan; Sukartha, I Made (E-Jurnal Akuntansi, 2016)
Aims of this research to recognize the influence of Local Tax, Local Retribution, and Audit Opinion for Expenditure Performance of Regional Government. Object of this research is the entire district governance and city governance in Bali Province. Data source of this research documented from Statistic Department Bali Province about the Realization of Local Revenue and Expenditure Report from year 2008 until 2013. This research tool use Multiple Regression Analysis. Total amount of data reseach as much as 54 data. The result of this research indicate that the Local Tax show negative influence for Expenditure Performance. Local Retribution didn't give influence for Expenditure Performance. Audit Opinion didn't give influence for Expenditure Performance.
Keywords: local tax, local retribution, audit opinion, expenditure performance